Commissioning and acceptance guide for the GammaPod. (21st October 2019) - Becker, Stewart; Sabouri, Pouya; Niu, Ying; Prado, Karl; Chen, Shifeng; Nichols, Elizabeth; Yi, ByongYong
Abstract: The GammaPod breast treatment device has been introduced to provide stereotactic radiation therapy to the breast to patients in the prone position. The GammaPod, using a stereotactic coordinate system, dynamically delivers dose to the target by rotating 25 non-overlapping Co-60 beams while the patient's breast is translated continuously in three axes on the couch during delivery. From simulation to treatment, the patient's breast is immobilized using mild negative pressure (150 mm Hg below atmospheric pressure) through a device-specific dual-cup system with stereotactic fiducials. This technology can be used for boost, multi-fraction partial-breast steterotactic body radiotherapy (SBRT), or single-fraction stereotactic radiosurgery (SRS). This paper reports the commissioning of the system for clinical use. The GammaPod device has four major subsystems: mechanical, dosimetric, radiation safety, and safety interlocks. Detailed methods for testing each subsystem have been identified and quantified. Mechanical systems include couch motion and accuracy along with couch sag. Dosimetric tests include absolute dose calibration, dose profiles, timer error, and plan verifications. Radiation safety includes room and wall surveys, along with device leakage measurements. Safety interlocks deal with power systems, immobilization, and treatment interrupts. The absolute dose rate of the 25 mm collimator was determined using TG-21 dosimetry protocol. The relative output factor for the 15 mm collimator was 0.94. The difference of the full-width-at-half-maximum of the single shot of the 25 mm collimator between the treatment planning system and the measurement was 0.2 mm. All interlocks were found to perform correctly, and the shield was within state and Nuclear Regulatory Commission limits. The items and techniques for commissioning the GammaPod have been developed and tested using the methods reported here.